Preparation method of VOCs adsorbent NaY@ZIF-8

By covering ZIF-8 on the NaY surface to form the core-shell adsorbent NaY@ZIF-8, the problem of degradation of existing VOCs adsorbents during high-temperature desorption is solved, and the adsorption performance is improved and cost is reduced. In industrial production.

CN117899841BActive Publication Date: 2024-12-31NANJING TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311787794.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2024-12-31
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

The existing VOCs adsorbents break chemical bonds during high-temperature desorption, resulting in poor recycling performance and high preparation cost, making it difficult to widely use in industrial production.

Method used

Precrystallization and step-by-step temperature-controlled crystallization methods are used to wrap ZIF-8 on the surface of NaY to form core-shell adsorbent NaY@ZIF-8, which improves the specific surface area and pore volume of the adsorbent, enhances its cycle stability and adsorption performance. .

Benefits of technology

It significantly improves adsorption performance and cycle stability, reduces preparation costs, makes it suitable for industrial mass production, can effectively improve the saturated adsorption capacity of toluene, and maintains good performance under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004625563290000071
    Figure BDA0004625563290000071
  • Figure BDA0004625563290000081
    Figure BDA0004625563290000081
  • Figure BDA0004625563290000082
    Figure BDA0004625563290000082
Patent Text Reader

Abstract

The present invention relates to a preparation method of a composite VOCs adsorbent NaY@ZIF‑8. It is characterized in that attapulgite is used as a silicon-aluminum source, a NaY molecular sieve is prepared by a crystallization reaction, and ZIF‑8 is successfully grown in situ on its surface by pre-crystallization and two-step temperature control means to prepare a composite VOCs adsorbent NaY@ZIF‑8. The silicon-aluminum source used in the patent of the present invention is rich in resources, low in price, and environmentally friendly. The prepared adsorbent has a large saturated adsorption capacity for toluene and good regeneration stability, and is suitable for industrial mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention patent relates to a method for preparing VOCs, and in particular to a method for preparing a core-shell VOCs adsorbent NaY@ZIF-8. Background Art

[0002] Volatile organic compounds (VOCs) are atmospheric pollutants with a boiling point of 50 to 260°C at normal temperature and pressure. Their anthropogenic sources mainly include the production and manufacturing of the coating industry and exhaust emissions from aircraft and motor vehicles. With the continuous deepening of my country's urbanization process, the impact of VOCs on ambient air quality has become increasingly prominent. Long-term exposure to an environment polluted by volatile organic compounds will cause damage to the human respiratory and immune systems, and eventually induce cancer. In addition, the presence of VOCs will also cause pollution to the atmosphere, water bodies and soil. Therefore, the control of VOCs has become a major problem that needs to be urgently solved in contemporary air pollution, and it is of great significance to adopt appropriate methods to effectively control it.

[0003] Adsorption method is one of the efficient means for purifying large air volume and low concentration VOCs waste gas. Molecular sieve has the characteristics of regular pore structure, excellent thermal stability, large specific surface area, etc., and is one of the ideal materials as VOCs adsorbent. Molecular sieve is usually made by hydrothermal crystallization of silicate and aluminate in a certain proportion. The main chemical components of attapulgite are SiO2 (about 60wt%) and Al2O3 (about 10wt%). High-temperature calcination can destroy the crystal structure of attapulgite and release SiO2 and Al2O3. my country has abundant natural deposits of attapulgite, and its price is 1 / 4 of the common industrial aluminosilicates. It is an excellent raw material for preparing molecular sieves.

[0004] In order to improve the efficiency of VOCs waste gas removal and further improve the adsorption performance of molecular sieves, a lot of related research work has been carried out. Lu et al. (Chemical Engineering Journal 409 (2021) 128194) increased the specific surface area and pore volume of the material by growing organic porous polymers on the surface of Y molecular sieves, thereby increasing the saturated adsorption capacity of the adsorbent for toluene from 106 mg / g to 182.3 mg / g.

[0005] Lu et al. (Chemical Engineering Journal 471(2023)144570) used different organic monomers to polymerize hypercrosslinked resin on the surface of Y molecular sieve to increase the pore volume and specific surface area of ​​the material, increasing its saturated adsorption capacity for toluene from 125.5 mg / g to 154 mg / g. However, the chemical bonds of organic porous polymers generally break at 200°C, and the temperature for desorption and regeneration of adsorbents in industry is generally 200-250°C, resulting in poor recycling performance of the material. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a core-shell VOCs adsorbent NaY@ZIF-8 using attapulgite as a raw material. Reduce the cost of adsorbent preparation and improve adsorption performance and cycle stability. ZIF-8 is a metal organic framework with a pyrolysis temperature between 300 and 400°C. This patent successfully wraps ZIF-8 of different thicknesses on the NaY surface through pre-crystallization and step-by-step temperature-controlled crystallization treatment, thereby increasing the specific surface area and pore volume of the adsorbent, which not only effectively improves the adsorption performance, but also ensures the cyclic stability of the material, making it better suitable for actual industrial production.

[0007] The technical solution of the present invention is: a method for preparing a composite VOCs adsorbent NaY@ZIF-8, and the specific steps are as follows:

[0008] (1) calcining attapulgite at high temperature in a muffle furnace to obtain pretreated attapulgite, mixing the pretreated attapulgite with sodium hydroxide and deionized water, stirring and refluxing for a period of time, ultrasonicating, centrifuging, and taking the upper layer of gel as a silicon-aluminum source;

[0009] (2) diluting the silicon-aluminum source with deionized water, transferring it to a hydrothermal reactor for crystallization for a certain period of time, filtering, washing, and drying to obtain a NaY molecular sieve;

[0010] (3) dissolving 2-methylimidazole and zinc nitrate hexahydrate in methanol to obtain solution A and solution B respectively;

[0011] NaY was mixed with solution A and solution B, and NaY powder with ZIF-8 seeds was obtained after ultrasonication, centrifugation and drying;

[0012] (4) mixing the NaY powder with ZIF-8 seeds with solution A and solution B in a certain mass volume ratio, stirring at low temperature, then transferring to room temperature for stirring, filtering, washing, and drying;

[0013] (5) Alternatively, steps (3) and (4) are repeated to obtain NaY@ZIF-8(x).

[0014] Preferably, the calcination temperature described in step (1) is 500-650° C., and the calcination time is 0.5-2 hours; the mass volume ratio of the pretreated attapulgite to deionized water is 0.25-0.3 g / mL; the mass volume ratio of sodium hydroxide to deionized water is 0.3-0.4 g / mL; the reflux time is 3.5-5 hours; the ultrasonic time is 0.5-2 hours; the centrifugal speed is 1000-4000 rpm, and the centrifugal time is 0.5-2 hours.

[0015] Preferably, the mass ratio of deionized water to silicon-aluminum source in step (2) is 1:(2-3); the crystallization temperature is 90-120° C.; and the crystallization time is 24-72 hours.

[0016] Preferably, in step (3), the mass volume ratio of zinc nitrate hexahydrate to methanol in solution A is 25:(0.2-0.5) mL / g; the mass volume ratio of 2-methylimidazole to methanol in solution B is 75:(0.3-0.6) mL / g; the mass volume ratio of NaY to solution A is 0.5:(1-3) g / mL; the mass volume ratio of NaY to solution B is 0.5:(3-5) g / mL; the ultrasonic time is 5-20 minutes; and the drying temperature is 80-100°C.

[0017] Preferably, the mass ratio of the NaY powder with ZIF-8 seeds in step (4) to the volume ratio of solution A is 0.5:(22-24) g / mL; the mass ratio of the NaY powder with ZIF-8 seeds to the volume ratio of solution B is 0.5:(70-72) g / mL; the low temperature is -15--5°C, the stirring speed is 200-400 rpm, and the stirring time is 2-4 hours; the room temperature stirring speed is 200-400 rpm, and the room temperature stirring time is 2-4 hours; the drying temperature is 80-100°C, and the drying time is 12-24 hours.

[0018] Preferably, in step (5), step (3) and step (4) are repeated 1 to 5 times.

[0019] Beneficial Effects

[0020] (1) The present invention uses attapulgite as a raw material to prepare the adsorbent, which has the advantages of abundant resources, low price, and green environmental protection.

[0021] (2) The adsorbent prepared by the present invention has a core-shell structure, which can effectively improve the saturated adsorption capacity of toluene and has good cyclic stability.

[0022] (3) The adsorbent prepared by the present invention has low cost and simple preparation method, which is conducive to industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Fixed bed adsorbent evaluation device; including 1. toluene standard gas; 2. high purity nitrogen; 3. mass flow meter; 4. stop valve; 5. three-way ball valve; 6. adsorption fixed bed; 7. gas chromatograph. DETAILED DESCRIPTION

[0024] Example 1

[0025] (1) 100 g of attapulgite was calcined in a muffle furnace at 500° C. for 2 hours to obtain pretreated attapulgite. 10 g of the pretreated attapulgite, 40 mL of deionized water, and 12 g of sodium hydroxide were mixed evenly, refluxed for 3.5 hours, ultrasonicated for 2 hours, and centrifuged at 4000 rpm for 30 minutes to obtain the upper layer of gel as the silicon-aluminum source.

[0026] (2) Add 10 g of deionized water to 20 g of the silicon-aluminum source, stir vigorously and evenly, then transfer to a polytetrafluoroethylene-lined reactor and crystallize at 90° C. for 72 hours, filter, wash and dry to obtain NaY molecular sieve.

[0027] (3) 0.5 g of zinc nitrate hexahydrate was dissolved in 25 mL of methanol to obtain solution A, and 0.6 g of 2-methylimidazole was added to 75 mL of methanol to obtain solution B. 0.5 g of NaY powder, 3 mL of solution A, and 5 mL of solution B were mixed, and after ultrasonication for 20 minutes, the mixture was quickly transferred to 100 °C to evaporate the solvent, thereby obtaining NaY powder with ZIF-8 seeds.

[0028] (4) 0.5 g of powder, 22 mL of solution A, and 70 mL of solution B were mixed, stirred at -15°C and 200 rpm for 4 hours, and then transferred to room temperature and stirred at 200 rpm for another 4 hours. The mixture was filtered, washed, and dried at 100°C for 12 hours to obtain NaY@ZIF-8.

[0029] Example 2

[0030] (1) 100 g of attapulgite was calcined in a muffle furnace at 550° C. for 1.5 hours to obtain pretreated attapulgite. 10 g of the pretreated attapulgite, 40 mL of deionized water, and 12 g of sodium hydroxide were mixed evenly. The mixture was refluxed for 4 hours, ultrasonicated for 1.5 hours, and centrifuged at 3000 rpm for 1 hour to obtain the upper layer of gel as the silicon-aluminum source.

[0031] (2) Add 10 g of deionized water to 20 g of the silicon-aluminum source, stir vigorously and evenly, then transfer to a polytetrafluoroethylene-lined reactor and crystallize at 100° C. for 48 hours, filter, wash, and dry to obtain a NaY molecular sieve.

[0032] (3) 0.4 g of zinc nitrate hexahydrate was dissolved in 25 mL of methanol to obtain solution A, and 0.5 g of 2-methylimidazole was added to 75 mL of methanol to obtain solution B. 0.5 g of NaY powder, 3 mL of solution A, and 5 mL of solution B were mixed, and after ultrasonication for 20 minutes, the mixture was quickly transferred to 100 °C to evaporate the solvent, thereby obtaining NaY powder with ZIF-8 seeds.

[0033] (4) 0.5 g of powder, 22 mL of solution A, and 70 mL of solution B were mixed, stirred at -15°C and 200 rpm for 4 hours, then transferred to room temperature and stirred at 200 rpm for another 4 hours. The mixture was filtered, washed, and dried at 100°C for 12 hours.

[0034] (5) Repeat steps (3) and (4) once to obtain NaY@ZIF-8(Ⅰ).

[0035] Example 3

[0036] (1) 100 g of attapulgite was calcined in a muffle furnace at 600° C. for 1 hour to obtain pretreated attapulgite. 15 g of the pretreated attapulgite, 50 mL of deionized water, and 20 g of sodium hydroxide were uniformly mixed. After 4.5 hours, the mixture was ultrasonicated for 1 hour, and the mixture was centrifuged at 2000 rpm for 1.5 hours to obtain the upper layer of gel as the silicon-aluminum source.

[0037] (2) Add 10 g of deionized water to 30 g of the silicon-aluminum source, stir vigorously and transfer to a polytetrafluoroethylene-lined reactor for crystallization at 110° C. for 36 hours, filter, wash and dry to obtain NaY molecular sieve.

[0038] (3) 0.35 g of zinc nitrate hexahydrate was dissolved in 25 mL of methanol to obtain solution A, and 0.45 g of 2-methylimidazole was added to 75 mL of methanol to obtain solution B. 0.5 g of NaY powder, 2 mL of solution A, and 4 mL of solution B were mixed, and after ultrasonication for 15 minutes, the mixture was quickly transferred to 90° C. to evaporate the solvent, thereby obtaining NaY powder with ZIF-8 seeds.

[0039] (4) 0.5 g of powder, 23 mL of solution A and 71 mL of solution B were mixed, stirred at -10°C and 300 rpm for 3 hours, then moved to room temperature and stirred at 300 rpm for another 3 hours. The mixture was filtered, washed and dried at 90°C for 18 hours.

[0040] (5) Repeat steps (3) and (4) twice to obtain NaY@ZIF-8(Ⅱ).

[0041] Example 4

[0042] (1) 100 g of attapulgite was calcined in a muffle furnace at 650° C. for 30 minutes to obtain pretreated attapulgite. 15 g of the pretreated attapulgite, 50 mL of deionized water, and 20 g of sodium hydroxide were uniformly mixed. The mixture was refluxed for 5 hours and then ultrasonicated for 30 minutes. The mixture was centrifuged at 1000 rpm for 2 hours to obtain the upper layer of gel as the silicon-aluminum source.

[0043] (2) Add 10 g of deionized water to 30 g of the silicon-aluminum source, stir vigorously and evenly, then transfer to a polytetrafluoroethylene-lined reactor and crystallize at 120° C. for 24 hours, filter, wash and dry to obtain NaY molecular sieve.

[0044] (3) 0.3 g of zinc nitrate hexahydrate was dissolved in 25 mL of methanol to obtain solution A, and 0.4 g of 2-methylimidazole was added to 75 mL of methanol to obtain solution B. 0.5 g of NaY powder, 2 mL of solution A, and 4 mL of solution B were mixed, and after ultrasonication for 15 minutes, the mixture was quickly transferred to 90° C. to evaporate the solvent, thereby obtaining NaY powder with ZIF-8 seeds.

[0045] (4) 0.5 g of powder, 23 mL of solution A and 71 mL of solution B were mixed, stirred at -10°C and 300 rpm for 3 hours, then moved to room temperature and stirred at 300 rpm for another 3 hours. The mixture was filtered, washed and dried at 90°C for 18 hours.

[0046] (5) Repeat steps (3) and (4) three times to obtain NaY@ZIF-8 (III).

[0047] Example 5

[0048] (1) 100 g of attapulgite was calcined in a muffle furnace at 600° C. for 1 hour to obtain pretreated attapulgite. 15 g of the pretreated attapulgite, 50 mL of deionized water, and 17.5 g of sodium hydroxide were mixed evenly, refluxed for 4.5 hours, ultrasonicated for 1 hour, and centrifuged at 2000 rpm for 1.5 hours to obtain the upper layer of gel as the silicon-aluminum source.

[0049] (2) Add 10 g of deionized water to 30 g of the silicon-aluminum source, stir vigorously and transfer to a polytetrafluoroethylene-lined reactor for crystallization at 110° C. for 36 hours, filter, wash and dry to obtain NaY molecular sieve.

[0050] (3) 0.25 g of zinc nitrate hexahydrate was dissolved in 25 mL of methanol to obtain solution A, and 0.35 g of 2-methylimidazole was added to 75 mL of methanol to obtain solution B. 0.5 g of NaY powder, 1 mL of solution A, and 3 mL of solution B were mixed, and after ultrasonication for 10 minutes, the mixture was quickly transferred to 80° C. to evaporate the solvent, thereby obtaining NaY powder with ZIF-8 seeds.

[0051] (4) 0.5 g of powder, 24 mL of solution A and 72 mL of solution B were mixed, stirred at -5°C and 400 rpm for 2 hours, then transferred to room temperature and stirred at 400 rpm for another 2 hours. Filtered, washed, and dried at 80°C for 24 hours.

[0052] (5) Repeat steps (3) and (4) four times to obtain NaY@ZIF-8 (Ⅳ).

[0053] Example 6

[0054] (1) 100 g of attapulgite was calcined in a muffle furnace at 600° C. for 1 hour to obtain pretreated attapulgite. 15 g of the pretreated attapulgite, 50 mL of deionized water, and 17.5 g of sodium hydroxide were mixed evenly, refluxed for 4.5 hours, ultrasonicated for 1 hour, and centrifuged at 2000 rpm for 1.5 hours to obtain the upper layer of gel as the silicon-aluminum source.

[0055] (2) Add 10 g of deionized water to 30 g of the silicon-aluminum source, stir vigorously and transfer to a polytetrafluoroethylene-lined reactor for crystallization at 110° C. for 36 hours, filter, wash and dry to obtain NaY molecular sieve.

[0056] (3) 0.2 g of zinc nitrate hexahydrate was dissolved in 25 mL of methanol to obtain solution A, and 0.3 g of 2-methylimidazole was added to 75 mL of methanol to obtain solution B. 0.5 g of NaY powder, 1 mL of solution A,

[0057] The solid obtained by centrifugation was quickly transferred to 80 °C to evaporate the solvent to obtain NaY powder with ZIF-8 seeds.

[0058] (4) 0.5 g of powder, 24 mL of solution A and 72 mL of solution B were mixed, stirred at -5°C and 400 rpm for 2 hours, then transferred to room temperature and stirred at 400 rpm for another 2 hours. Filtered, washed, and dried at 80°C for 24 hours.

[0059] (5) Repeat steps (3) and (4) five times to obtain NaY@ZIF-8(V).

[0060] Comparative Example 1

[0061] The preparation method is the same as that of Example 1, except that steps (3) and (4) are omitted.

[0062] Comparative Example 2

[0063] The preparation method is the same as that of Example 2, except that steps (3), (4) and (5) are omitted.

[0064] Comparative Example 3

[0065] The preparation method is the same as that of Example 3, except that steps (3), (4) and (5) are omitted.

[0066] Comparative Example 4

[0067] The preparation method is the same as that of Example 4, except that steps (3), (4) and (5) are omitted.

[0068] Comparative Example 5

[0069] The preparation method is the same as that of Example 5, except that steps (3), (4) and (5) are omitted.

[0070] Comparative Example 6

[0071] The preparation method is the same as that of Example 6, except that steps (3), (4) and (5) are omitted.

[0072] Adsorption performance evaluation: Figure 1 The fixed bed adsorption device shown in the figure evaluates the performance of the adsorbent. Toluene standard gas and high-purity nitrogen are mixed in a certain proportion to the inlet concentration through a mass flow meter. After the inlet concentration is stable for ten minutes, the three-way ball valve is connected to the adsorption fixed bed to start the experiment; when the outlet concentration is equal to the inlet concentration, the three-way ball valve is switched to bypass and the experiment is stopped.

[0073] Adsorption capacity evaluation: 0.1g of adsorbent was loaded into a quartz tube, and glass wool was used to fix the adsorbent at both ends. The inner diameter of the quartz tube was 9mm, the adsorbent particle size was between 20 and 40 meshes, and the adsorption temperature was controlled by a high and low temperature constant temperature bath. The toluene concentration at the inlet of the equipment was 200ppm, the air velocity was 90000mL / (g·h), and the adsorption temperature was 25°C. The concentration of toluene at the outlet was detected by gas chromatography, and the saturated adsorption capacity was calculated according to the following formula.

[0074]

[0075] Where: Q is the saturated adsorption capacity, mg / g; C0 is the inlet concentration of toluene, mg / m 3 ; Ci is the outlet concentration at time i, mg / m 3 ;t s is the time required for adsorption to reach saturation, min; F is the gas flow rate through the adsorption column, mL / min; w is the mass of the loaded adsorbent, g.

[0076] Cyclic stability evaluation: When the adsorption reaches saturation, close the stop valve on the toluene standard gas pipeline. Raise the temperature to 250°C and purge with 50mL / min of high-purity nitrogen for 2 hours for desorption. After desorption is completed, wait for the temperature to drop to 25°C and evaluate the adsorption performance again. Repeat this process for 5 cycles to evaluate the cyclic stability of the adsorbent.

[0077] The saturated adsorption capacity of toluene by the 12 adsorbents prepared in the examples and comparative examples is shown in Table 1. Figure 1 and its description.

[0078] Table 1 Saturated adsorption capacity of toluene by the adsorbents prepared in the examples and comparative examples

[0079]

[0080] From the comparison results in Table 1, it can be seen that coating ZIF-8 on the surface of NaY can significantly increase the saturated adsorption capacity of the adsorbent for toluene. The saturated adsorption capacity of toluene of the NaY@ZIF-8 (III) sample of Example 4 is as high as 210.8 mg / g, which is 79.2% higher than that of the corresponding control sample.

[0081] The samples of Example 1 and Example 4 with the best and worst adsorption performance were selected for cyclic stability evaluation. The results are shown in Table 2.

[0082] Table 2 5 cycle test results of Example 1 and Example 4

[0083]

[0084] As shown in Table 2, after 5 rounds of adsorption-desorption cycle tests, the saturated adsorption performance of toluene did not decrease significantly, indicating that the prepared adsorbent has good cyclic stability.

Claims

1. A method for preparing a composite VOCs adsorbent NaY@ZIF-8, the specific steps of which are as follows: (1) calcining attapulgite at high temperature in a muffle furnace to obtain pretreated attapulgite, mixing the pretreated attapulgite with sodium hydroxide and deionized water, stirring and refluxing for a period of time, ultrasonicating, centrifuging, and taking the upper layer of gel as a silicon-aluminum source; (2) diluting the silicon-aluminum source with deionized water, transferring it to a hydrothermal reactor for crystallization for a certain period of time, filtering, washing, and drying to obtain a NaY molecular sieve; (3) dissolving 2-methylimidazole and zinc nitrate hexahydrate in methanol to obtain solution A and solution B respectively; mixing NaY with solution A and solution B, and obtaining NaY powder with ZIF-8 seeds after ultrasonication, centrifugation and drying; (4) mixing the NaY powder with ZIF-8 seeds with solution A and solution B in a certain mass volume ratio, stirring at low temperature, then transferring to room temperature for stirring, filtering, washing, and drying to obtain NaY@ZIF-8; (5) Repeat steps (3) and (4) to obtain the composite VOCs adsorbent NaY@ZIF-8.

2. The preparation method according to claim 1, characterized in that: The calcination temperature described in step (1) is 500-650° C., and the calcination time is 0.5-2 hours; the mass volume ratio of the pretreated attapulgite to deionized water is 0.25-0.3 g / mL; the mass volume ratio of sodium hydroxide to deionized water is 0.3-0.4 g / mL; the reflux time is 3.5-5 hours; the ultrasonic time is 0.5-2 hours; the centrifugal speed is 1000-4000 rpm, and the centrifugal time is 0.5-2 hours.

3. The preparation method according to claim 1, characterized in that: The mass ratio of deionized water to silicon-aluminum source in step (2) is 1:(2-3); the crystallization temperature is 90-120° C.; and the crystallization time is 24-72 hours.

4. The preparation method according to claim 1, characterized in that: The mass ratio of zinc nitrate hexahydrate to methanol in solution A described in step (3) is (0.2-0.5):25 g / mL; the mass ratio of 2-methylimidazole to methanol in solution B is (0.3-0.6):75 g / mL; the mass ratio of NaY to solution A is 0.5:(1-3) g / mL; the mass ratio of NaY to solution B is 0.5:(3-5) g / mL; The ultrasonic time is 5 to 20 minutes; the drying temperature is 80 to 100°C.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the NaY powder with ZIF-8 seeds in step (4) to solution A is 0.5:(22-24) g / mL; the mass ratio of the NaY powder with ZIF-8 seeds to solution B is 0.5:(70-72) g / mL; the low temperature is -15--5°C, the stirring speed is 200-400 rpm, and the stirring time is 2-4 hours; the room temperature stirring speed is 200-400 rpm, and the room temperature stirring time is 2-4 hours; the drying temperature is 80-100°C, and the drying time is 12-24 hours.

6. The preparation method according to claim 1, characterized in that: The number of times of repeating steps (3) and (4) described in step (5) is 1 to 5 times.

Citation Information

Patent Citations

  • Synthesis method of Y type molecular sieve

    CN103043679A

  • Y / EU-1 / SBA-15 / ASA / MOF composite material and preparation method thereof

    CN107519933A

  • Method for regulating ZIF-8 crystal morphology by utilizing surfactant

    CN107722046A

  • Low-temperature plasma synergistic catalyst for treating VOCs as well as preparation method and application of low-temperature plasma synergistic catalyst

    CN114247466A

  • Method for converting high-acid-value algal oil by molecular sieve in-situ growth two-dimensional ultrathin nanosheet

    CN114574288A